Analisis Tingkat Efektivitas Penggunaan Mikrotrans JakLingko Sebagai Penunjang Mobilitas - Habel, Rizki Hamdallah; Mahendra, Fikri Aditya; Nugraha, Adelio Shatara (Peneliti.net, 2024)
This study aims to measure the effectiveness of JakLingko microtransit use in the community. Community activities always involve movement every day, from economic activities to social activities. The method used in this research is quantitative research method, the samples taken in this study were UNJ students who used JakLingko in traveling to campus. In the research, the data used is primary data obtained by distributing questionnaires to respondents. From the results of the conclusions that can be drawn, the microtrans program has met the ratio of being very effective and has achieved the objectives of the JakLingko microtrans program itself. With the results of this study, it shows that the JakLingko microtrans at the effectiveness level shows positive results for its existence as a mode of transportation.